2013
DOI: 10.1039/c3nr00990d
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale fractionation of nanodiamonds by density gradient ultracentrifugation

Abstract: Size is a defining characteristic of nanoparticles; it influences their optical and electronic properties as well as their interactions with molecules and macromolecules. Producing nanoparticles with narrow size distributions remains one of the main challenges to their utilization. At this time, the number of practical approaches to optimize the size distribution of nanoparticles in many interesting materials systems, including diamond nanocrystals, remains limited. Diamond nanocrystals synthesized by detonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Chemical composition and sample cleanliness of as-prepared DNDs, prepared by the established procedure, [26] was studied with XPS ( Fig. S1) and showed that the DNDs mainly comprise of C, with small amounts of O, N, and traces of Cl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical composition and sample cleanliness of as-prepared DNDs, prepared by the established procedure, [26] was studied with XPS ( Fig. S1) and showed that the DNDs mainly comprise of C, with small amounts of O, N, and traces of Cl.…”
Section: Resultsmentioning
confidence: 99%
“…The DNDs, purchased from Sigma Aldrich, were prepared by rate-zonal density gradient ultracentrifugation, described elsewhere [26].…”
Section: Detonation Nanodiamonds (Dnds) Preparationmentioning
confidence: 99%
“…[167] Another strategy incorporates sacrificial bonds, such as coordination bonds, [156] hydrogen bonds, [168] or imine bonds, [157] in polyfluorene-based supramolecular copolymers. [174] Other examples that employ aqueous density-gradient media include MoS 2 nanosheets, [175] nanodiamonds, [176] zeolite nanosheets, [177] and Fe/Co graphitic-shell nanocrystals. [156,157,168] Density-gradient ultracentrifugation (DGU), developed initially for biochemistry, [149,169] is another separation strategy based on centrifugation, which utilizes density-gradient media to influence the motion of nanomaterials in centrifugal fields.…”
Section: Separation Methods For Improving Nanomaterials Monodispersitymentioning
confidence: 99%
“…Another protocol was developed by Mahfouz et al [27] including cycles of grinding, chemical purification and fractioning by ultracentrifugation [28]. HPHT diamond microparticles (size 210-250 μm) with a nitrogen concentration of 200 ppm were used as raw material.…”
Section: From Hpht Diamondmentioning
confidence: 99%